Climate-driven patterns of global tree longevity - Jiani Gao; Keyan Fang; Jing M. Chen; Jinbao Li; Sergio Rossi; Deliang Chen; Hans W. Linderholm; Jesús Julio Camarero; Jan Esper; Nicole K. Davi; Tsun Fung Au; Zhengtang Guo (Communications Earth & Environment)
Abstract Concerns about climate change-influenced tree growth declines and world tree mortality raise questions about potential reductions in tree longevity. However, the global influences of climate and growth patterns on tree longevity remain poorly understood. Here we analyzed 219,000 tree-ring widths from 4880 globe sites, encompassing 246 species, to investigate tree longevity patterns. Gymnosperms exhibited significantly greater average longevity (366 ± 240 years) than angiosperms (216 ± 81 years), with the oldest individual exceeded 3000 years. Globally, gymnosperm longevity was negatively correlated with precipitation. Arid-adapted trees exhibited significantly higher longevity, likely due to their conservative growth strategy, characterized by slow growth rates and enhanced drought resilience. Trees in harsh environments defined by high altitude, nutrient-poor soils, and minimal human impact were more likely to attain greater longevity. These findings highlight the impact of climate change on tree longevity and the necessity for targeted conservation strategies to protect these vital ecosystem components.